The predictors of defensive pessimism: Cognitive flexibility, anxiety, and big-five personality traits - YÜKSEL, MÜGE; EKŞİ, HALİL (My University, 2022)
This study aims to investigate the predictor power of cognitive flexibility, anxiety, and neuroticism, and openness personality traits on defensive pessimism in the context of a high-stakes test. For this purpose, the study conducts the adaptation of the Defensive Pessimism Questionnaire (DPQ) and the Cognitive Flexibility Inventory (CFI), and measures the validity and reliability of these tools on Turkish teenagers. The participants in the study consisted of three independent groups of participants with a total number of 1361 students enrolling at high schools. The DPQ, CFI, Big-Five Inventory, and Trait-State Anxiety Scale were administered to the participants. The findings demonstrated that the factor structures of both scales were similar to the original forms, and both of the scales had a high level of validity and reliability. The study also concluded that cognitive flexibility, anxiety, and personality explained 44% of defensive pessimism after a regression analysis.
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Social Sciences and Humanities; Psychology; PSİKOLOJİ, MULTİDİSİPLİNER; Temel Bilimler (SCI); PSYCHOLOGY, MULTIDISCIPLINARY; PSYCHOLOGY; Natural Sciences (SCI); Genel Psikoloji; Psikoloji (çeşitli); Sosyal Bilimler ve Beşeri Bilimler; General Psychology; Psychology (miscellaneous); Social Sciences & Humanities; Defensive pessimism; cognitive flexibility; anxiety; personality traits; high-stakes tests; OPTIMISM; SELF; NEUROTICISM; MOOD; LIFE; RELIABILITY; STRATEGIES; DIMENSIONS; COMPLEXITY; BEHAVIOR